Assessment and optimisation of human walking and traffic induced vibration of floors in office buildings - Tuan Chik, Tuan Norhayati (2022)
Rapid development in office building construction and advanced technologies installed in sensitive structures such as high-tech equipment leads to requirements for very low levels of vibration and become more important in structural design. Therefore, this thesis presents an investigation of vibration criteria assessment and optimisation of the effect of low amplitude ground vibrations induced by human walking and traffic on the floors in office building. Two office buildings were chosen as the case study at two different places namely OB1 and OB2. Field measurement was carried out by using Laser Doppler Vibrometer (LDV100) to obtain vibration inputs. Vibration inputs were transferred into finite element analyses by using ANSYSv14 to simulate the structure dynamic response. MATLAB software also utilized to perform Vibration Criteria (VC) curve and plot. The results obtained were then checked against the generic VC curve from Gordon and Malaysia guidelines, to determine the vibration sensitivity level of each building. As a result, OB1 indicated under VC-A level due to vehicles at Singapore and OB2 at Malaysia fall under VC-E due to vehicles and increased to VC-C, VC-A and ISO level due to peoples walking. It is also showing which location on floor is suitable to accommodate the sensitive equipment, but not at the middle of the floor because of the peak response. After the modification process on structural elements such as slab thickness, beam and column sizes, and adding extra elements, the vibration response also changed either increased or decreased from the earlier VC curve and plot. OB1 shows almost similar vibration level under VC-A. While for OB2, it is also indicating similar response under VC-E. Therefore, from the iterative process in finite element modelling from the optimisation method, a VibroTable is proposed to be a new guideline or quick review to the client or structure analyst engineer to investigate the proper size of certain element of structure. The difference of vibration velocity values between Gordon and Malaysian guidelines were found, where Gordon guideline covers very low level of vibration effect, while Malaysian guideline only considers high level of vibration.